2012
DOI: 10.1080/13674676.2011.581273
|View full text |Cite
|
Sign up to set email alerts
|

Parental object representations, attachment to God, and recovery among individuals with psychosis

Abstract: This study explored the relationships between object representations of mother and father and recovery among outpatients with psychotic disorders, and examined the role of attachment to God in moderating those relationships. A total of 46 outpatients diagnosed with schizophrenia or schizoaffective disorder participated. Benevolent representations of mother and father were associated with recovery whereas punitive representations were negatively associated with recovery. Secure attachment to God amplified the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Other studies have also shown associations between schizotypal traits and positive religious experience (cf. Bennett et al, 2013; Prout et al, 2012, 2016). From a psychodynamic perspective, patients with severe personality pathology and/or psychotic vulnerability might idealize/depersonalize God into a God representation of a nebulous, schizotypal quality (Goodman and Manierre, 2008) to defend against NAs (Descôteaux et al, 2001; Kernberg, 1976).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also shown associations between schizotypal traits and positive religious experience (cf. Bennett et al, 2013; Prout et al, 2012, 2016). From a psychodynamic perspective, patients with severe personality pathology and/or psychotic vulnerability might idealize/depersonalize God into a God representation of a nebulous, schizotypal quality (Goodman and Manierre, 2008) to defend against NAs (Descôteaux et al, 2001; Kernberg, 1976).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In terms of treatment, the work toward more stability and recovery with patients with psychotic PO could be aided by explicitly tapping into the compensation function of religion (if positive God representations are present) and by helping patients (and their families) mobilize the supportive possibilities of a religious community. Among patients with this severe form of psychopathology, higher levels of faith in God and experiencing a relatively secure attachment relationship with God are associated with more confidence in treatment and higher levels of recovery (Prout et al, 2012, 2016; Rosmarin et al, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nove estudos (DUMONT et al, 2012;ELLISON et al, 2014;REINER et al, 2010;WEI et al, 2012;BRADSHAW et al, 2010;ELLISON et al, 2012;PROUT et al, Tanto Bradshaw et al (2010) como Ellison et al (2012) pesquisaram a associação entre apego a Deus e angústia. Ambos os estudos concordam que um apego seguro a Deus está associado com a redução da angústia e que um apego seguro a Deus amortece os efeitos danosos de eventos estressantes da aflição (BRADSHAW et al, 2010, p. 1;ELLISON et al, 2012, p. 493).…”
Section: Demais Estudos Em Saúde Mentalunclassified
“…Christian faith, for example, elevates the paradox of the cross and the resurrection of Jesus, and people facing every type of suffering (including mental illness) have found solace and empowering hope in the gospel narrative. 35 Religion is not the only basis for transcendent meaning. The shared struggle against social exclusion and cultural prejudice has empowered many people to re-author their personal story, as people with disabilities (including mental illness) form communities of power to bring about political and socio-cultural change.…”
Section: Happiness Pleasure and Meaningmentioning
confidence: 99%